Utilization of genetic information for medicines development and equitable benefit sharing - Matsuyama, Kotone; Kurihara, Chieko; Crawley, Francis P.; Kerpel-Fronius, Sandor (Frontiers in Genetics, 2023)
Advances in genomic research have significantly enhanced modern drug development. However, equitable benefit-sharing of the results of scientific advancement has not always been achieved. This paper shows how molecular biology has modified medicines' development while also leaving open significant challenges for benefit sharing. Presented here is a conceptual modeling describing the processes in genetic-related medicines development and how these are related to specific ethical considerations. The focus is on three important areas: (1) population genetics and the need for discrimination prevention; (2) pharmacogenomics and the need for inclusive governance; and (3) global health to be achieved in open science frameworks. Benefit sharing is taken as the ethical value that underlies all these aspects. The implementation of benefit sharing requires a value shift in which the outcomes of health science are not viewed simply as trade commodities but also as a “global public good”. This approach should lead to genetic science to contribute to promoting the fundamental human right to health to all members of the global community.